Metabolites of the Soy Sauce Koji Making with Aspergillus niger and Aspergillus oryzae. (28th October 2021) - Hu, Wenkang; Liu, Zeping; Fu, Bin; Zhang, Xiaolong; Qi, Yonggang; Hu, Yong; Wang, Chao; Li, Dongsheng; Xu, Ning
Abstract: Koji making comprises multi‐microbial interactions and is an important part of soy sauce production. The aim of this study was to determine interactions and investigate metabolites in koji by ultra‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry (UPLC‐Q/TOF‐MS). Differential metabolites between groups of single strain ( Aspergillus oryzae ) and mixed strains ( Aspergillus niger and A. oryzae ) koji making were screened and identified using an untargeted metabolomics approach to evaluate microbial interaction. A. oryzae was the dominant strain in koji mixed fermentation. Growth of both fungal species occurred rapidly during the initial 24 h of fermentation and then stabilised. Inoculation of A. niger led to changes in the contents of dipeptides, flavonoids, unsaturated fatty acids, carotenoids, phenols and indoles in koji . These differences could be attributed to glycerophospholipid and glycerolipid m4etabolism, as well as to pantothenate and CoA biosynthesis of A. niger . Abstract : Soy sauce koji were making by single strain ( Aspergillus oryzae ) and mixed strains ( Aspergillus niger and A. oryzae ). Differential metabolites of koji were screened and identified to evaluate microbial interaction.